The nature of Islamic education - Ahmad Sudan, Salmi (Center for Promoting Ideas, USA, 2017)
Education is a transmission of values and knowledge. It involves teaching, learning, socialization and enculturation. Islamic education is comprehensive (shamil), balanced, and it targets personality development, cognizant mind set, patriotism, open-mindedness, intellectual, spiritual and harmonious coexistence. Education in Islam focuses on beneficial knowledge which has a direct influence on the receiver. It moulds both the intellectual faculties and character of the individual. The best educator in Islam was Prophet Muhammad and he is a perfect role model for all teachers (uswatanhassanah) and educators. He was able to educate humans through the Qur’an and the hadith, the fundamental sources of Islamic education, through action and speech and through wisdom, with its diverse levels and varieties. It is important to note that Islamic education is not mere memorization of some Islamic texts; rather it is the comprehensive and conscious understanding of all aspects of life